2007
DOI: 10.1016/j.cardiores.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Early electrical remodeling in rabbit pulmonary vein results from trafficking of intracellular SK2 channels to membrane sites

Abstract: Objective: Atrial fibrillation is often initiated by bursts of ectopic activity arising in the pulmonary veins. We have previously shown that a 3-h intermittent burst pacing protocol (BPP), mimicking ectopic pulmonary vein foci, shortens action potential duration (APD) locally at the pulmonary vein-atrial interface (PV) while having no effect elsewhere in rabbit atrium. This shortening is Ca 2+ dependent and is prevented by apamin, which blocks small conductance Ca 2+ -activated K + channels (SK Ca ). The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 33 publications
3
126
1
1
Order By: Relevance
“…24 Later, 1 study implied a link between SK channels and AF pathogenesis by providing evidence that increased SK2 channel cell-membrane trafficking and thereby elevation of calcium-activated potassium currents by intermittent burst pacing at the pulmonary vein-atrium interface provided an arrhythmogenic substrate for AF. 25 Interestingly, another report illustrated that genetic knockout of SK2 channels caused prolongation of action potential duration in atrial myocytes, and then AF. 26 Furthermore, another study also showed that pharmacological inhibition of SK channels resulted in prolongation of the atrial effective refractory period, thereby inhibiting reentry, and then AF prevention and termination.…”
Section: Discussionmentioning
confidence: 99%
“…24 Later, 1 study implied a link between SK channels and AF pathogenesis by providing evidence that increased SK2 channel cell-membrane trafficking and thereby elevation of calcium-activated potassium currents by intermittent burst pacing at the pulmonary vein-atrium interface provided an arrhythmogenic substrate for AF. 25 Interestingly, another report illustrated that genetic knockout of SK2 channels caused prolongation of action potential duration in atrial myocytes, and then AF. 26 Furthermore, another study also showed that pharmacological inhibition of SK channels resulted in prolongation of the atrial effective refractory period, thereby inhibiting reentry, and then AF prevention and termination.…”
Section: Discussionmentioning
confidence: 99%
“…This APD shortening was inhibited by apamin, a blocker of the calcium-activated potassium channels. 31 This provides a possible basis of KCNN3 having a role in AF. The SNP rs3807989 is located close to the gene CAV1-encoding caveolin.…”
Section: The 4q25 Locusmentioning
confidence: 94%
“…90,91 One important factor could be the shorter action potential duration (APD) of the PVs vs the atrium 84 due to larger delayed-rectifier K + currents and smaller inward Ca 2+ currents in the PV. 89,92,93 In addition, PVs demonstrate conduction abnormalities that promote reentry due to abrupt changes in fiber orientation as well as Na + channel inactivation by reduced resting potentials due to small I K1 . 84 Yet another study examined the impact of increasing atrial pressure on PV activation, finding that as LA pressure was increased above 10 cm H 2 O, the PV–LA junction became the source of dominant rotors.…”
Section: Section 2: Definitions Mechanisms and Rationale For Af Ablmentioning
confidence: 99%